Thermodynamical characterization of poly (ethylene glycol) and tosylate functionalized poly(ethylene glycol) interaction with some nonpolar and polar solvents via inverse gas chromatography - Sesigur, Feyza; Dasdan, Dolunay Sakar; Yazici, Ozlem; Cakar, Fatih; Cankurtaran, Ozlem; Karaman, Ferdane (NATL INST OPTOELECTRONICS, 2016)
Tosylate functionalized poly(ethylene glycol) (PEG-Tos) which was synthesized via the tosylation of the corresponding poly(ethylene glycol) (PEG) with p-toluenesulfonyl chloride was thermodynamically characterized at temperatures in K between 303 and 373 by inverse gas chromatography technique (IGC). The retention diagrams of n-hexane, n-heptane, n-octane, n-nonane, n-decane, dichloromethane, chloroform, acetone, tetrahydrofuran, ethyl acetate and ethanol on the PEG and PEG-Tos were plotted between these temperature ranges. Some polymer-solvent thermodynamic interaction parameters, such as weight fraction activity coefficient, Omega(infinity)(1), Flory-Huggins polymer-solvent interaction parameters, Omega(infinity)(12) were determined for studied solvents at infinite dilution of PEG and PEG-Tos at temperatures above mentioned. Then, the partial molar heat of sorption, Delta(H) over bar (s)(1), the partial molar heat of mixing at infinite dilution, Delta(H) over bar (infinity)(1) and as well as the molar heat of vaporizations of solvents, Delta(H) over bar (v) were determined. In addition, the solubility parameter of PEG and PEG-Tos delta(2) was determined at room temperature by extrapolation of the values of solubility parameters from studied temperatures to 298 K.
Keywords: Poly (ethylene glycol); p-toluenesulfonyl poly(ethylene glycol); Inverse gas chromatography; Polymer-solvent interactions; Solubility parameter; SOLUBILITY PARAMETERS; Materials Science; Optics